Cranial morphology of Jonkeria truculenta (Titanosuchidae, Therapsida, Dinocephalia) and a taxonomic reassessment of the family - Jirah, Sifelani; Rubidge, Bruce S; Abdala, Fernando (Evolutionary Studies Institute, 2023)
Titanosuchidae are a group of derived herbivorous long snouted dinocephalians currently only known from the South African Karoo. Taxonomic revision of the Titanosuchids, for the first time accompanied by detailed anatomical descriptions and illustrations of representative cranial material, enabled recognition of only two species out of the nine previously recognized. These are Titanosuchus ferox and Jonkeria truculenta. Jonkeria vanderbyli, Jonkeria ingens, Jonkeria haughtoni, Jonkeria parva, Jonkeria rossouwi and Jonkeria boonstrai are here, synonymized with Jonkeria truculenta. The species Jonkeria koupensis is a nomen dubium only identified as Titanosuchid indet. Cranial characters, which modify during ontogenetic development, were, recognized for Jonkeria truculenta, and for the first time an ontogenetic growth series is, presented for this species.
Keywords: Dinocephalia; Titanosuchidae; Beaufort Group; Tapinocephalus Assemblage Zone